Total tubeless percutaneous nephrolithotomy without artificial hydronephrosis in preschool children: Three case reports. Issue 13 (31st March 2023) - Zhang, Xicai; Zhang, Yonghe; Li, Fengyue; He, Wenbo; Cao, Xiande
Abstract : Rationale: Indwelling ureteral catheter, double J tube, or nephrostomy tube are routine procedures for percutaneous nephrolithotomy (PCNL) in children. There are a few cases in which PCNL has been performed in children without any additional instruments being left in place. Patient concerns: In this study, 3 children were treated for hematuria and complicated with different degrees of urinary tract infection. All of them were diagnosed as upper urinary tract calculi by abdominal computed tomography. Diagnosis: Three preschoolers were diagnosed with upper urinary tract calculi before surgery, one with no hydronephrosis and the other 2 with different degrees of hydronephrosis. Interventions: After preoperative evaluation, all the children successfully completed PCNL without indwelling ureteral catheter, double J tube, or nephrostomy tube. Outcomes: The operation was successful and there were no residual stones observed during postoperative review. The operating times for the children were 33 minutes, 17 minutes, and 20 minutes, and the intraoperative bleeding volumes were 1 mL, 2 mL, and 2 mL. The catheter was removed on the second day after the operation, the postoperative review of the abdominal computed tomography or ultrasound did not indicate any stone residue, and there were no fever, bleeding, and other related complications after the operation. Lessons: We believe that total tubeless PCNL without artificial hydronephrosis can be achieved in the preschool population.